The Effect of Shear Sliding of Vertical Contraction Joints on Seismic Response of High Arch Dams with Fine Finite Element Model - Shengshan Guo; Jianxin Liao; Hailong Huang; Hui Liang; Deyu Li; Houqun Chen; Aijing Zhang; Yifu Tian (Advances in Civil Engineering, 2020)
The contraction joints of arch dams with and without shear keys are simplified to be with no-slip condition and with relative sliding condition, respectively. Based on the Lagrange multiplier method, a contact model considering the manner of independent cantilever dead load type with no-slip condition and relative sliding condition is proposed to model the nonlinearities of vertical contraction joins, which is special to the nonlinear analysis of arch dams considering the manner of dead load type. Different from the conventional Gauss iterative method, the strategy of the alternating iterative solution of normal force and tangential force is employed. The parallelization based on overlapping domain decomposition method (ODDM) and explicit message passing using distributed memory parallel computers is employed to improve the computational efficiency. An existing high arch dam with fine finite element model is analyzed to investigate the effect of shear sliding of vertical joints on seismic response of the arch dam. The result shows that the values of maximum principal tensile stress under relative sliding condition are significantly greater than those under no-slip condition.